Analisis Dampak Fatherless terhadap Kondisi Sosioemosional Remaja - Ghina Hanifah; Gadies Reva Dhea M; Bilqis Syakira Khalda; Alfan Darojatul Ulya; Naufaldy Nurrobi Aditya; Siti Hamidah (Jurnal Psikoedukasi dan Konseling, 2025)
The absence of a father figure physically, emotionally and psychologically impacts the psychological development of individuals, especially adolescents. Fatherless is a term used for individuals who have unfavorable emotional experiences due to lack of affection from their father. The loss of the father's role is not only caused by death or divorce, but fathers who do not have time to interact with children also cause adolescents to experience fatherless conditions. This study was designed to assess the impact of fatherlessness on adolescents' socioemotional state by reviewing and interpreting available research using the Systematic Literature Review method. The articles were then analyzed and summarized in this study. It was found that children, especially adolescents who experience the fatherless phenomenon, will experience symptoms such as loneliness, jealousy, anxiety, and depression. This statement shows that the loss of the father's role in the life of adolescents can have an impact in socioemotional aspects.